Cell Phone Cities and Smartphone Pedestrians. - Sneep, Deirdre (Steiner, 2017)
A Tokyo case study on the influence of smartphones on everyday city life: It takes a closer look at the perceived dangers of smartphone use in the city.
Keywords: Stadtplanung; Stadtentwicklung; Verkehrsplanung; Kommunikationstechnologie; Telekommunikation; Fußgängerverkehr; Fahrradverkehr; Stadtgestaltung; Smart City; Smartphone; Telefonieren; Interaktion; Alltagsleben; Nutzerfreundlichkeit